Pengetahuan Metakognitif Mahasiswa Pendidikan Fisika - Abdullah, Hemi; Amin, Bunda Dara (Indonesian Journal of Educational Studies, 2016)
This study aims to reveal the student metacognitive knowledge Physics Education. Study ekspolorasi made against 20 students of third semester Physical Education Studies by giving Metacognitive Knowledge Test with Harmonic Vibration Unit. The results show that turned out to be as much as 0.00% could not answer with a perfect. This result shows that the impact of learning physics for two semesters not contributed to the development of metacognitive knowledge. The further observation Â found that the cause of students not able to complete the test is due to their lessons during the teaching staff is more oriented to the teacher Â learning center is dominated in explaining the theories without facilitating the development of metacognitive knowledge